Hydrocracking Boscan heavy oil with catalysts containing a zeolite component. - Minja, Rwaichi J. A. (University of Ottawa (Canada), 1990)
In this study, hydrodesulphurization (HDS), hydrodenitrogenation (HDN), hydrodemetallization (HDM), and micro carbon residue (MCR) removal were investigated using residuum hydrocracking catalysts containing a zeolite component. The first family of catalysts containing H-mordenite was tested at a pressure of 13.9 MPa and at temperatures of 400 and 450$\sp\circ$C in an upward flow packed bed reactor. The results showed increased overall HDM, but decreased overall HDS, HDN, and MCR removal with increasing catalyst H-mordenite content. Analysis based on constant residence time and constant catalyst surface area, i.e., calculation of pseudo turnover frequency (PTOF) and PTOF per unit residence time, showed increased catalyst activity for all reactions with increasing catalyst H-mordenite content. The second family of catalysts containing HY was tested at the same conditions, but at temperatures of 400 and 370$\sp\circ$C. For these catalysts there was similar results compared to the first family of catalysts. Benzofuran temperature programmed desorption (TPD) measurements showed that, the number of acid sites increased with increasing zeolite (H-mordenite or HY) content in the catalysts. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.